Current biological therapies and malignancy risk - Majtas, Adrian; Możdżan, Zofia; Zheng, Edward; Olejnik, Agnieszka; Gajewski, Dominik; Tambor, Jakub; Tambor, Igor; Nowosielska-Ogórek, Agnieszka; Gronek, Konrad; Huszcza, Beata (Quality in Sport, 2026)
Background. Biological therapies and small-molecule inhibitors have transformed the treatment of chronic inflammatory diseases, though long-term malignancy risks remain a clinical concern. This review evaluates the oncogenic risks of major classes, including TNF-α, interleukin (IL), and Janus kinase (JAK) inhibitors, alongside B-cell depleting agents. While TNF-α and JAK inhibitors may increase certain skin cancers or lymphomas in specific populations, IL-17 and IL-23 inhibitors maintain a favorable safety profile. Paradoxically, controlling chronic inflammation can reduce the risk of inflammation-driven malignancies like colorectal cancer. Aim. To evaluate the malignancy risks of major therapeutic classes (TNF-α, IL, and JAK inhibitors), focusing on clinically significant cancers like HSTCL and skin malignancies, while assessing modifying factors such as age and cumulative exposure. Material and methods. A narrative literature review was conducted using clinical trials, meta-analyses, and observational data from PubMed and the Cochrane Library. Results were synthesized narratively due to study heterogeneity, methodological constraints, and short follow-up periods. Results. TNF-α and JAK inhibitors are associated with an increased risk of non-melanoma skin cancer (NMSC) and certain lymphomas. In contrast, IL-17 and IL-23 inhibitors show safety profiles consistent with baseline population rates. Hepatosplenic T-cell lymphoma (HSTCL) is almost exclusively linked to combination therapy with thiopurines. Effectively neutralizing chronic inflammation can lower the risk of certain cancers, such as colorectal cancer. Conclusions. Biological therapies generally do not increase the risk of solid tumors above baseline. Aggressive oncological risks are typically driven by concomitant therapies (e.g., thiopurines) or the underlying disease itself. Regular dermatological and gynecological screening remains essential to balance therapeutic efficacy with safety.